Micromorphology and phytochemical screening of Piper betle L. (Piperaceae) - Thu, Do Thi Anh; Lý Hồng Hương, Tran Trung Trinh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Piper betle L., a common species in many countries, is used in many traditional medicines of countries and in many social, cultural, and religious ceremonies. P. betle has many traditional effects such as colds, bronchial asthma, cough, abdominal pain, rheumatism, bad breath, constipation, conjunctivitis, swollen gums, abscesses, and wound healing... Identifying P. betle species correctly is important for these activities, so this study aims to strengthen the criteria for accurate identification of P. betle species further. P. betle leaves were described microbiologically by staining sections, examining P. betle leaf powder and preliminary phytochemical composition of the leaves by modified Ciuley method. Microscopic characteristics of P. betle roots, stems, and leaves, microscopic characteristics of leaves include xylem-phloem in the leaf microstructure, a layer of palisade tissue present in the leaf anatomy, leaves powder (characterized by soft tissue fragments with colored masses, spiral veins), and preliminary chemical composition including essential oils, coumarins, flavonoids, organic acids, reducing agents and polyuronics. The study provides additional data on microscopic characteristics and chemical composition in the leaves of P. betle species.